Pelatihan Penggunaan Sistem Informasi Akademik Berbasis Website (Profile Sekolah) - Bakaruddin; Rahmi, Rahmiati; Putri, Rizki Amelia (ISEI Cabang Pekanbaru, Koordinator Provinsi Riau, 2023)
Information technology has become an important part of all sectors, including the development of education. The school profile website is a new form of school identity in the current information era, so that information about the school can be easily found. By implementing a website application, it can help school administrators improve their abilities in the field of technology and information. This training method is felt to be very effective in delivering material, and then the administrators or school staff carry out the practice according to the directions.